2021
DOI: 10.1111/hel.12842
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Aquaporin 5 by carcinogenic Helicobacter pylori infection promotes epithelial‐mesenchymal transition via the MEK/ERK pathway

Abstract: Background Helicobacter pylori (H. pylori) is a major risk factor for gastric cancer. The water channel protein Aquaporin 5 (AQP5) is involved in the tumorigenesis and progression of various cancers. In this study, we aimed to explore the role of AQP5 in H. pylori‐induced gastric carcinogenesis. Materials and Methods We collected 160 samples which inculded CNAG, IM, Dys and gastric cancer from patients who underwent endoscopy and detected the expression of AQP5. In vivo and vitro H. pylori infection models, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…The finding in the present study uncovered that AQP5 was upregulated in gastric mucosa and GECs infected with H. pylori . Similarly, a published work has also revealed that AQP5 expression elevates in GECs in gastritis, which is related with the H. pylori infection [ 9 ]. Moreover, it was found that silencing of AQP5 could restrain levels of inflammatory factor (TNF-α and IL-1β) and apoptosis of GECs in mice with H. pylori -related gastritis.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The finding in the present study uncovered that AQP5 was upregulated in gastric mucosa and GECs infected with H. pylori . Similarly, a published work has also revealed that AQP5 expression elevates in GECs in gastritis, which is related with the H. pylori infection [ 9 ]. Moreover, it was found that silencing of AQP5 could restrain levels of inflammatory factor (TNF-α and IL-1β) and apoptosis of GECs in mice with H. pylori -related gastritis.…”
Section: Discussionmentioning
confidence: 93%
“…It is interesting to note that H. pylori infection could elevate Aquaporin 5 (AQP5) expression in gastric epithelial cells (GECs), which promotes the development of gastritis [ 9 ]. AQP5, a member of AQPs, is essential for regulating water transport in healthy tissues and is related to multiple human cancers, such as gastric cancer [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower levels of miR-877 and miR874, shown to regulate AQP3 and AQP5 expression, respectively, may account for the increased AQP3 and AQP5 expression and epithelial mesenchymal transition [114,115]. AQP3 and AQP5 expression has been shown to be positively correlated with gastric mucosal disease progression in gastric carcinoma and other stages of gastric diseases as well as with Helicobacter pylori infection [116,117]. Helicobacter pylori promote AQP3 and AQP5 expression (through the activation of downstream HIF-1α or ERK1/ 2, MEK, respectively) that could be used as novel molecular targets for therapeutic interventions [116,117].…”
Section: Gastric Glandsmentioning
confidence: 99%
“…AQP3 and AQP5 expression has been shown to be positively correlated with gastric mucosal disease progression in gastric carcinoma and other stages of gastric diseases as well as with Helicobacter pylori infection [116,117]. Helicobacter pylori promote AQP3 and AQP5 expression (through the activation of downstream HIF-1α or ERK1/ 2, MEK, respectively) that could be used as novel molecular targets for therapeutic interventions [116,117]. Furthermore, as the expression of certain AQPs is associated with better or poor overall survival of patients with gastric cancer, it can be used as predictive prognostic gastric cancer biomarker [110,118].…”
Section: Gastric Glandsmentioning
confidence: 99%